Evaluating the impact of nature-based solutions on the provision of water-related and water-dependant ecosystem services - Raquel Marijuan; Bárbara Díez; Sara Peláez-Sánchez; Claudia Sánchez; Jesús Iglesias; Başar Şirin; Alper Baba; Orhan Gündüz; Raúl Sánchez (Nature-Based Solutions)
Water scarcity is a pressing issue in the Mediterranean region, exacerbated by overuse of resources for agriculture and the impacts of climate change. Addressing this challenge requires improved water cycle management and the adoption of Nature-based Solutions (NbS) to enhance infrastructure efficiency and sustainability. With the aim of promoting the implementation and assessment of NbS, we have developed a monitoring framework that integrates the assessment of ecological, socio-economic and cultural aspects under the umbrella of the IUCN Global Standard for NbS. A list of Key Performance Indicators (KPIs) was selected following standard methodologies. We have applied the framework to five case studies in the Mediterranean region to evaluate its efficiency to assess NbS tailored to local challenges and contexts. As part of the monitoring framework, we used the IUCN self-assessment tool for the Global Standard for NbS, demonstrating adherence of 50–75 % across all case studies. Common KPIs were identified, streamlining monitoring efforts and providing guidance from the design phase onwards. Our monitoring framework offers a comprehensive approach to evaluating NbS interventions, ensuring alignment with global standards and enhancing resilience in water management. By integrating the IUCN Global Standard, it provides robust guidance for future execution, contributing to sustainable water resource management in the Mediterranean and beyond.